Lester Frank Ward papers - Ward, Lester Frank, 1841-1913.; Ward, Lester Frank, 1841-1913.; Ward, Lester Frank, 1841-1913.; Ward, Lester Frank, 1841-1913.; Ward, Lester Frank, 1841-1913.; Ward, Lester Frank, 1841-1913.
Drafts, notes, and page proofs of Ward's books: Dynamic Sociology (1883), Psychic Factors of Civilization (1893), Outlines of Sociology (1898), Pure Sociology (1903), and Applied Sociology (1906). The materials trace the development of Ward's beliefs regarding egalitarian sociology.
Sociologist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Sociology; Sociologists